Metode Pembelajaran Calistung Melalui Alat Permainan Edukatif (APE) Dengan Barang Bekas Di SD Inpres Kehiran, Sentani - Irfan Wahyudi; Radian J. Situmeang; Ida M. Hutabarat; Yacob Ruru; Natasya I. Parenden; Lintia N. Santi (JURNAL PENGABDIAN PAPUA, 2025)
Children's ability to read, write and count (calistung) can be said to be very important in life, because the teaching and learning process or activity is based on reading ability. To support learning and to know the growth and development of children, teachers and parents should know the right method or way to teach children to read, write and count. One method or way to develop it is through educational game tools (APE). First grade students at SD Inpres Kehiran have quite low learning abilities. This can be seen from almost 60% of students still having difficulty reading, writing and counting and is indicated by the scores obtained which are still below the Minimum Completion Criteria that have been set. To help teachers and students at SD Inpres Kehiran in understanding reading, writing and counting, our Community Service Team (PKM) aims to introduce the use of simple educational game tools (APE) made from used materials, namely through letter cards, drink bottle caps, and objects around the school or around the student's residential environment. By using learning media through educational game tools, the effectiveness of the learning method is evaluated and the level of student participation is measured. The stages carried out in the implementation of this community service activity start from planning, namely by coordinating with the school and asking permission from the leader (Dean), then the implementation stage starts from preparing materials, tools and materials, training and mentoring and finally the reporting stage, namely making a final report and making publications. The methods used to support the success of this program are in the form of training, demonstrations and practice questions. The implementation of this Community Service has not fully achieved the expected targets and outputs, but this activity has made a positive contribution to students in terms of recognizing letters, spelling, reading and simple arithmetic.